Antioxidant, antidiabetic, anti-inflammatory and anticancer potential of some seaweed extracts - SHAFAY,Shimaa EL (2022)
Abstract This study aims to evaluate the secondary metabolites, cytotoxicity, antioxidant, antidiabetic, anti-inflammatory, and anticancer activities of four selected seaweeds Padina pavonica, Taonia atomaria, Jania rubens, and Corallina elongata. The maximum value of phenolic content (176.7 ± 6.9 mg gallic acid equivalents/g crude extract) and tannin content (26.5 ± 4.3 mg tannic acid equivalents/g crude extract), was shown in the methanol extract of J. rubens and P. pavonica, respectively. While the ethanol extract of T. atomaria recorded the highest values of total flavonoid content (374.1 ±27.4 mg quercetin equivalents/g crude extract) and total saponins content (30.2 ± 0.7 mg cholesterol equivalents/g crude extract, respectively) compared to other seaweeds. Methanol extract of J. rubens and C. elongata exhibited the greatest content of alkaloids (25.8 ± 4.4 and 22.7 ± 2.6 mg/g d wt.). The methanol extract of P. pavonica established the highest DPPH radical scavenging activity (55.7% ± 0.1) at 50 μg/mL. Among the selected seaweed extracts, the ethanol extract of T. atomaria demonstrated the maximum α-amylase inhibition capacity (66.3% ± 0.0). Methanol extract of J. rubens and P. pavonica species effectively prevented the hypotonicity-induced haemolysis in a concentration-dependent manner compared with the diclofenac potassium as a standard anti-inflammatory drug. In vitro, the reported results also supported the safety and non-toxicity of the four seaweed extracts on WI-38 cell line at lower concentrations. J. rubens and P. pavonica methanol extracts recorded the highest cell growth inhibition of the HeLa Cancer Cell Lines compared to other seaweed extracts and the standard drug Cisplatin.